2005
DOI: 10.1021/jf052035u
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Uropathogenic Escherichia coli by Cranberry Juice:  A New Antiadherence Assay

Abstract: A combination of microplate technology and turbidity assessment for testing the adherence of P-fimbriated Escherichia coli to human uroepithelial cell line T24, validated with the addition of the known inhibitor 4-O-alpha-D-galactopyranosyl-alpha-D-galactopyranose (galabiose), resulted in a high-throughput, biologically relevant assessment of cranberry (Vaccinium macrocarpon). P-fimbriated ATCC E. coli strains 25922, 29194, and 49161 were inhibited by galabiose. ATCC 29194, a representative urine isolate conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 57 publications
0
44
0
Order By: Relevance
“…40 In brief, p-fimbriated E. coli were grown on CFA agar to promote fimbrial growth. Human T-24 cells were grown to confluence in 96-well microplates.…”
Section: Biological Activitymentioning
confidence: 99%
“…40 In brief, p-fimbriated E. coli were grown on CFA agar to promote fimbrial growth. Human T-24 cells were grown to confluence in 96-well microplates.…”
Section: Biological Activitymentioning
confidence: 99%
“…Our research group recently found that the crude extract of title plant and its sub-fractions had promising antioxidant activities (IC 50 =26.44, 15.72 µg/mL, for crude extract and EtOAc layer, respectively). Herein, we report the bioassay-directed fractionation leading to the isolation of two new lignan glycosides (1, 2), along with fourteen known compounds including 4 lignanoids: dihydrodehydodiconiferyl alcohol (3), 10) (+ )-lyoniresinol-3α-O-α-L-rhamnoside (4), 11) 5-methoxy-(+ )-isolariciresinol-9′-O-α-L-rhamnoside (5), 12) (+ )-acviculin (6) 12) ; 5 triterpenoids: batrogenic acid (7), 13) trachelosperogenin A (8), 14) paradrymonoside (9), 15) 24-epipinfaensin (10), 16) rosamultin (11) 17) ; 2 flavonoids: arimadendrin (12), 18) naringenin-7-O-β-D-glucoside (13) 19) ; 2 aromatics:…”
mentioning
confidence: 99%
“…In designing an assay to measure inhibition of E. coli adherence to a human uroepithelial cell line [15], it was determined that, at sufficiently low pH, the cranberry constituent benzoic acid and its urinary metabolite hippuric acid have bacteriostatic and/or bactericidal activity. The search for anti-adherent compounds was thus confounded by the presence of benzoic acid, which apparently killed the bacteria before they could be inhibited from adhering.…”
Section: Cranberries As Antibacterial Agentsmentioning
confidence: 99%
“…The full details of this assay are described elsewhere [15] but, in brief, the procedure is as follows: Immortalized human uroepithelial T24 cells (ATCC HTB4) were grown to confluence in wells of a microplate. A urinary E. coli (ATCC 29194) isolate containing the uropathogenic papGII gene was grown on CFA agar, suspended in saline to 10 7 bacteria per mL, mixed with test cranberry fractions, and incubated with the T24 cells for 1 hour.…”
Section: Anti-adhesion Assaymentioning
confidence: 99%
See 1 more Smart Citation